Comparison of surgical resection of Axillary Lymph Nodes in Dogs with Mammary Gland Tumors with or without sentinel lymph node visualization with patent blue dye - Souza, Mayara Coutinho Carlo de; Flecher, Mayra Cunha; Arrais, Fernanda Ming; Sena, Bruna Voltolin de; Giuliano, Antonio; Horta, Rodrigo dos Santos (Frontiers in Veterinary Science, 2023)
The axillary lymph node (ALN) in dogs is often difficult to locate before surgical resection. The anatomical location of ALN often discourages its removal by many veterinarians. Considering the limited literature available, the real incidence of metastases and the prognostic importance of their evaluation is still not well established. A non-randomized, prospective clinical study was carried out with female dogs (n=41) with mammary gland tumor (MGT) in the thoracic or cranial abdominal mammary glands. The main objective of this study was to compare ALN resection with or without patent blue 2.5% (PB) dye injection for sentinel lymph node visualization. The secondary objective of the study was to assess the risks of ALN metastasis based on tumors clinical findings, tumor size, histopathological diagnosis and grade. A total of 46 mastectomies were performed. In the first group, nineteen patients underwent a mastectomy and lymphadenectomy without PB injection (G1), while in the second group twenty-seven patients also received PB injection for sentinel lymph node mapping (G2). The ALN was identified in 38/46 cases (82%). The ALN was identified and excised in only 58% of surgeries in G1(19/46), while in group 2 the lymph node was identified in 92% of the cases and resected in 100% of the cases. Surgical time differed between the two groups, as it was significantly shorter in the PB injection group compared to group 1 (80 vs. 45 minutes) (p <0.0001). Macroscopic abnormalities in the lymph nodes, tumor size (>3cm), and diagnosis of anaplastic carcinoma or grade II/III mammary gland tumors were associated with a higher probability of ALN metastasis. The use of PB improves ALN´s identification and reduces the surgical resection time in dogs with MGT. Metastases in the ALNs are more common, in dogs presenting with tumors larger than 3cm and diagnosed with aggressive histological subtypes. The use of PB staining is useful for the identification of the ALN in female dogs with MGT. Metastases are relatively frequent in the ALNs and they should be removed for the correct staging, prognostic evaluation, and decision for adjuvant therapy.